The Effect of Sales Promotion on Purchasing Decisions - Indri Suryani; Afriapollo Syafarudin (Yayasan Ilomata, 2021)
To trigger consumer transactions in order to buy a certain product and encourage aggressive purchasing decisions. One trick is that promotion is able to stimulate demand for a product. With the promotion, it is expected that consumers will want to try these products and encourage existing consumers to buy products more often so that re-purchases will occur and the sales volume of a company's products will increase. Promotion is an important factor in realizing the sales goals of a company. In order for consumers to be willing to subscribe, they must first be able to try or research the goods produced by the company, so that buyers can be sure of these goods. Targeted promotion is expected to have a positive effect on increasing sales. Promotion is an important aspect of marketing management and is often said to be a continuous process. With promotion, people who are not interested in buying a product will be interested and try the product so that consumers make a purchase. The type of promotional mix is ​​the combination of the best strategies from the variables of advertising, personal selling, and other promotional tools, all of which are planned to achieve the goals of the sales program. This study aims to examine the effect of promotion on glove purchasing decisions. Respondents of this study used 150 research samples at various hospitals, namely doctors and health workers, the tools used in this study used the PLS (Partial Least Square) analysis method. The results of this research are the effect of promotion on purchasing decisions accepted. Keywords: Sales Promotion, Purchasing Decision